2015
DOI: 10.1051/0004-6361/201525764
|View full text |Cite
|
Sign up to set email alerts
|

Searching for signatures of planet formation in stars with circumstellar debris discs

Abstract: Context. Tentative correlations between the presence of dusty circumstellar debris discs and low-mass planets have recently been presented. In parallel, detailed chemical abundance studies have reported different trends between samples of planet and non-planet hosts. Whether these chemical differences are indeed related to the presence of planets is still strongly debated. Aims. We aim to test whether solar-type stars with debris discs show any chemical peculiarity that could be related to the planet formation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
93
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(102 citation statements)
references
References 96 publications
8
93
0
1
Order By: Relevance
“…The authors concluded that the T c trend depends on the Galactic chemical evolution (GCE) and suggested that the difference in T c slopes, observed between planet hosting solar analogs and solar analogs without detected planets, may reflect their age difference. Maldonado et al (2015) and Maldonado & Villaver (2016) also confirmed the correlation of the T c trend with age, and further suggested a significant correlation with the stellar radius and mass. Önehag et al (2014) in turn showed that while the Sun shows a different T c trend when compared to the solarfield twins, it shows a very similar abundance trend with T c when compared to the stars from the open cluster M 67.…”
Section: Introductionsupporting
confidence: 55%
“…The authors concluded that the T c trend depends on the Galactic chemical evolution (GCE) and suggested that the difference in T c slopes, observed between planet hosting solar analogs and solar analogs without detected planets, may reflect their age difference. Maldonado et al (2015) and Maldonado & Villaver (2016) also confirmed the correlation of the T c trend with age, and further suggested a significant correlation with the stellar radius and mass. Önehag et al (2014) in turn showed that while the Sun shows a different T c trend when compared to the solarfield twins, it shows a very similar abundance trend with T c when compared to the stars from the open cluster M 67.…”
Section: Introductionsupporting
confidence: 55%
“…We also added individual objects with activity periods reported by Metcalfe et al (2010), DeWarf et al (2010), and Egeland et al (2015). We also included the parameters of HD 45184 that were determined by different literature works (Sousa et al 2008;Bensby et al 2014;Battistini & Bensby 2015;Maldonado et al 2015;Nissen 2015;Spina et al 2016). These are shown as blue filled circles with error bars.…”
Section: Discussionmentioning
confidence: 99%
“…The works of Meléndez et al (2009) and Ramírez et al (2009) have triggered several papers investigating relations between [X/Fe]-T C slopes and the existence of planets around stars (Gonzalez et al 2010;González Hernández et al 2010, 2013Schuler et al 2011;Adibekyan et al 2014;Maldonado et al 2015). The results obtained are not very conclusive, partly because the stars included span wider ranges in T eff , log g, and [Fe/H] than the solar twins in Meléndez et al (2009) making the abundance ratios less precise and introducing a dependence of the derived [X/Fe]-T C slopes on possible corrections for Galactic evolution effects.…”
Section: Introductionmentioning
confidence: 99%